Postural Instability Induced by Visual Motion Stimuli in Patients With Vestibular Migraine - Lim, Yong-Hyun; Kim, Ji-Soo; Lee, Ho-Won; Kim, Sung-Hee (Frontiers in Neurology, 2018)
Patients with vestibular migraine are highly susceptible to motion sickness. This study aimed to determine whether the severity of posture instability is related to the susceptibility to motion sickness. We used a visual motion paradigm with two conditions of the stimulated retinal field and the head posture to quantify postural stability while maintaining a static stance in 18 patients with vestibular migraine and in 13 age-matched healthy subjects and. Three parameters of postural stability showed differences between VM patients and controls: RMS velocity (0.34±0.02 cm/s versus 0.28±0.02 cm/s), RMS acceleration (8.94±0.74 cm/s2 versus 6.69±0.87 cm/s2), and sway area (1.77±0.22 cm2 versus 1.04±0.25 cm2). Patients with vestibular migraine showed marked postural instability of the head and neck when visual stimuli were presented in the retinal periphery. The pseudo-Coriolis effect induced by head roll tilt was not responsible for the main differences in postural instability between patients and controls. Patients with vestibular migraine seemed to have a higher visual dependency and low stability of the postural control system when maintaining quiet standing, which may be related to susceptibility to motion sickness.